Venom in Verse : Aristophanes in Modern Greece - Van Steen, Gonda Aline Hector, 1964- (Book collections on Project MUSE., 2000)
Aristophanes has enjoyed a conspicuous revival in nineteenth- and twentieth-century Greece. Here, Gonda Van Steen provides the first critical analysis of the role of the classical Athenian playwright in modern Greek culture, explaining how the sociopolitical "venom" of Aristophanes' verses remains relevant and appealing to modern Greek audiences. Deriding or challenging well-known figures and conservative values, Aristophanes' comedies transgress authority and continue to speak to many social groups in Greece who have found in him a witty, pointed, and accessible champion from their "native" t